Remote Learning Models in Video Corpus Construction: Simulation, Creativity and Remodelling as Pedagogic Tools - Taibi, Davide (Revija za elementarno izobraževanje, 2023)
Within online learning environments research, this paper identifies four remote-learning models that have characterised the use of the OpenMWS platform within the processes of selection, transcription, annotation and concordance-like searches characterising video corpus construction and analysis. They relate to student tasks such as the creation of video corpora ex novo when completing dissertations, traineeships, group project work and with remodelling existing video corpora to meet the needs of new audiences such as primary and secondary schoolchildren. The paper makes reference to how analytics records student interactions with the platform, an approach inviting students to reflect on their own learning trajectories.
Keywords: VCC (video corpus construction), OpenMWS platform, remote learning, learning environments specialised pedagogies.